Benefits of Bank Diversification: The Evidence from Shareholder Returns: Discussion - Brown, Stephen J. (Journal of Finance, 1984)
Stephen J. Brown, Benefits of Bank Diversification: The Evidence from Shareholder Returns: Discussion, The Journal of Finance, Vol. 39, No. 3, Papers and Proceedings, Forty-Second Annual Meeting, American Finance Association, San Francisco, CA, December 28-30, 1983 (Jul., 1984), pp. 893-894